Keratome, a Better Alternative Scalpel to No. 15 Blade for Finer Incision—Randomized Control Trial - Mohan, Amitabh; Rangwala, Murtuza; Boringwala, Abdul Q. (Indian Journal of Plastic Surgery, 2022)
Background Scalpel is the most common and oldest instrument used by surgeons for incision and to perform the surgery. A lot of improvement has occurred in the design of scalpel from the flint knife to the modern Bard-Parker handle with blades. The quest for improvement and finding a better instrument is neverending. In this study, we present an alternative scalpel to the no. 15 blade most commonly used by plastic surgeons.Material and Methods Consultants and residents in plastic surgery department used a no.15 blade and a 15-degree straight keratome on randomly selected patients and used subjective numerical rating scale to assess the ease of incision and dissection. The data were collected and statistically analyzed.Results In this study, 89 patients were included out of which 68 cases were operated by the consultants and 21 cases were operated by residents. The average score of ease of incision using a no. 15 blade by the consultants was 6.52 and by the residents was 6.125. The average score of ease of incision using a 15-degree straight keratome by the consultants was 8.74 and by the residents was 8.84. p-Value was statistically significant when no. 15 blades and 15-degree straight keratome were compared.Conclusion 15-degree straight keratome is an excellent scalpel that can be used in preference to no. 15 blade as it is difficult to use.
Keywords: scalpel; no. 15 blade; 15-degree straight keratome; incision; dissection